O nome das personagens em cinzas do Norte: uma questão poética - PINHEIRO, Lucilia Lúbia de Sousa (Universidade Federal do Pará, 2020)
The article presents the poetic form, according to Meschonnic (2002), of the names of the characters in Northern Ashes (2005), starting from the intention of the abstract author to intensify the name of the main character Mundo. Being constantly called by the nickname Mundo (World), the character conveys the experience he will have beyond Manaus, from the North to the world. The experiences that Mundo will have from these trips, as well as the very context in the work, place him as a character in a formation novel. Keywords: Name. Character. Northern Ashes. Poetic.